Cognitive Analytics in ESG Performance Measurement and Investment Decision-Making: The Moderating Role of Corporate Governance - Hendrarini Suryaningtiyas; Unggul Purwohedi; Ayatulloh Michael Musyaffi (Institut Bisnis dan Informatika Kesatuan, 2026)
This study aims to examine the role of cognitive analytics in measuring Environmental, Social, and Governance performance and its influence on investment decisions with corporate governance as a moderating variable. This study uses a qualitative approach in the form of library research with a systematic, analytical, and critical descriptive analysis method of relevant literature. Data were collected from 100 articles indexed in the Scopus database for the period 2022-2025, then analyzed using bibliometric analysis and data visualization through Harzing’s Publish or Perish and VOSviewer software. Governance was the most discussed topic, followed by ESG performance and investment decisions. English was the dominant language in publications, with the main fields of study being Business, Management, and Accounting. Publication trends showed a significant increase from year to year, especially in 2024 and 2025. Factors that shape ESG performance, as well as governance aspects such as board size and diversity. Investment decision-making, behavioral factors such as prospects, heuristics, and herding are the main focus. Corporate governance acts as a moderator that strengthens the relationship between ESG performance and investment decisions. An integrative conceptual model linking these three variables with cognitive analytics as a measurement and analysis tool is proposed to improve sustainable decision-making.